The ecological state of the Braamfontein spruit - an urban river - Fiddes, Kyle Brett (My University, 2019)
Urban environments are unique systems comprising many ecosystems. These ecosystems include urban rivers and green spaces (parks, green belts, gardens) which are important for the provision of ecosystem services and help increase city resilience to climate change. They have however come under pressure from development and have become severely degraded with many of the ecosystem services, being lost. The Braamfontein Spruit in Johannesburg, South Africa, is one such example of how developmental pressure impacts on river and riparian ecosystems. The aim of this study was to assess the current condition of the Braamfontein Spruit using the South African Scoring System 5 (SASS 5) and a River Health Assessment to determine if it was a viable system for restorative measures. The results showed that the river itself is seriously/ critically modified whilst the riparian and green spaces along its length are moderately modified. pH, conductivity and dissolved oxygen (DO) were found to be above limits considered to be natural while Average Score Per Taxon (ASPT) was below levels that indicate good water quality. Relationships between variables and taxa numbers were all negative with increases in pH, conductivity and DO resulting in fewer observed taxa. The main vegetation type found along the Spruit was grass, followed closely by bare ground. The observed patterns are due to issues such as land-use change, pollution (both point and non-point), urban development, surface runoff and poor maintenance. These aspects have impacted the tested variables resulting in a degraded ecosystem, however, the results suggest that the Braamfontein Spruit is a suitable option for restoration and proper environmental management if the necessary measures are taken. Measures recommended include clearing of litter and debris, improving river flow (creation of riffles and pools), reducing runoff and creating natural vegetation strips
A Dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Science. Johannesburg, 2019